Web-Based Training for an Evidence-Supported Treatment: Training Completion and Knowledge Acquisition in a Global Sample of Learners. (August 2015) - Heck, Nicholas C.; Saunders, Benjamin E.; Smith, Daniel W.
The purpose of this investigation is to describe the characteristics of professional and preprofessional learners who registered for and completed TF-CBTWeb, a modular, web-based training program designed to promote the dissemination of Trauma-Focused Cognitive Behavioral Therapy (TF-CBT) and to demonstrate the feasibility of this method of dissemination. Between October 1, 2005, and October 1, 2012, a total of 123, 848 learners registered for TF-CBTWeb, of whom 98, 646 (79.7%) initiated the learning activities by beginning the first module pretest. Of those, 67, 201 (68.1%) completed the full training. Registrants hailed from 130 countries worldwide, and they had varied educational backgrounds, professional identities (both professional and preprofessional), and a range of experience working with child trauma victims. Learners who were from the United States, students, those with master's degrees, and those with fewer years of experience working with child trauma victims tended to have the highest course completion rates. Learners displayed significant increases in knowledge about each component of TF-CBT, based on module pretest and posttest scores. The advantages and limitations of this web-based training program evaluation are discussed, while important implications for the use of web-based trainings are reviewed.